TRADING CHANNELS AND MARGINS OF BOVINE MILK IN GUASAGANDA PARISH, LA MANA CANTON, COTOPAXI, ECUADOR - Torres Navarrete, Emma Danielly (2015)
The aim of the research was to provide information on the characteristics of bovine milk marketing in Guasaganda parish, La Mana canton, Cotopaxi province, Ecuador. The methodology consisted in identifying marketing channels and establishing marketing margins in the area. It began with the identification of the origin of the product, its features, and systematic observation during all processes involving changes in form and properties until it reaches the final consumer. A survey of the different agents that perform marketing: producers (P), intermediaries (A), pasteurizer industry (IP) and artisan (IA) and retailers (D). Gross marketing margin (MBC), net marketing margin (MNC) was designed and implemented and the percentage of producer participation (PDP) was obtained. Besides production costs and profitability of a liter of milk at producer level were obtained. The results show the marketing of three products: raw milk, fluid milk and cheese.  Two main trading channels were determined: short channel (40% of smallholders: producer-final consumer) and  conventional channel (100% of medium and large producers and 60% of small producers: producer – rural gatherer - pasteurizer industry - retailer- final consumer two outlets were determined - final consumer (fluid milk) - producer - rural gatherer – cheese handicraft industry - retailer - final consumer). The gross trading margins of the fluid milk, on average, were: MBC (60%), PDP (40%) and MNC (38.7%) and the gross trading margins of cheese, on average, were: MBC (40.34%), PDP (59.66%) and MNC (29.8%).